2021
DOI: 10.7759/cureus.13767
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Sinus Thrombosis in COVID-19: An Unusual Presentation

Abstract: Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) has been associated with a significantly increased risk of venous and arterial thromboembolism, particularly in severely sick patients. Recently, cerebral venous sinus thrombosis (CVST) cases have been reported in the context of coronavirus disease-2019 (COVID-19). These cases either had an active COVID infection with a positive reverse transcriptionpolymerase chain reaction (RT-PCR) or were symptomatic (fever, respiratory symptoms, myalgia) during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The condition has also been linked to a wide range of viral infections, and according to the recent reports, COVID-19 can be considered as an independent risk factor for CVST as 75% of CVST in COVID-19 cases were not associated with any other identifiable risk factor [ 7 , 13 ]. The exact figure regarding the incidence of CVST in COVID-19 cases is yet to be available [ 14 ]. However, studies with different results have been published.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The condition has also been linked to a wide range of viral infections, and according to the recent reports, COVID-19 can be considered as an independent risk factor for CVST as 75% of CVST in COVID-19 cases were not associated with any other identifiable risk factor [ 7 , 13 ]. The exact figure regarding the incidence of CVST in COVID-19 cases is yet to be available [ 14 ]. However, studies with different results have been published.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of CVST include seizures, decreased consciousness, headache, focal neurological deficits, weakness of extremities, and disorientation, which may be missed during diagnosis in COVID-19 cases as they can also be associated with neurological manifestations [ 14 ]. The current case was oriented and conscious, but she was presented with headache, nausea, and slurred speech.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus may also increase the risk of coagulation through other unknown pathophysiological mechanisms [ 38 , 39 ]. The mechanism of coagulation by COVID-19 is initiated by the binding of spike surface protein of SARS-CoV-2 to human angiotensin-converting enzyme (ACE) 2 receptor, causing direct viral endothelial invasion, endothelial apoptosis, and neuronal damage [ 38 , 40 - 54 ]. Studies have found that infection with SARS-CoV-2 and activation of the coagulation cascade, cytokine storm-related prothrombotic state, and/or increased platelet activity can accelerate the progression of cerebrovascular events including CVST [ 6 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mostly used anticoagulant therapy was the heparins: enoxaparin 36% (13/36), low molecular weight heparin 28% (10/36), heparin 19% (7/36; undifferentiated Hughes et al 16 Garaci et al 63 Klein et al 38 Sugiyama et al 41 Hemasian and Ansari 60…”
Section: Summary Of the Data In Tablementioning
confidence: 99%